HUBUNGAN INDEKS MASSA TUBUH (IMT), LINGKAR LEHER DAN LINGKAR PERUT DENGAN RESIKO TERJADINYA OBSTRUCTIVE SLEEP APNEA (OSA) PADA PASIEN CORONARY ARTERY DISEASE (CAD) DI RSUP Dr. HASAN SADIKIN BANDUNG - Cahyati, Ai (Buletin Media Informasi, 2015)
Obstructive Sleep Apnea (OSA) can give complicated burdens on Coronary Artery Disease (CAD). This research aimed at indentifying factors which relate to risks of the occurrence of  OSA on patients with CAD.   This research employed Cross Sectional Design. The total of respondents were 161 respondents. The measurement of OSA risks was conducted using questionnaires. The result of data analyse identified that there is a significant correlation among IMT,  circle of neck and belly with the risks of OSA occurrence. Recommendation reveals that screening on the risks of OSA occurrence is needed for CAD patients.